PENERAPAN NILAI-NILAI “JAWARA” PADA PROGRAM STUDI ILMU ADMINISTRASI NEGARA FISIP UNTIRTA - Arenawati Arenawati; Yeni Widyastuti (Universitas Sultan Ageng Tirtayasa, 2014)
Universities are institutions that aim scored scholars with theoretical andpractical abilities . Theoretical and practical ability is not enough to make them jump insociety , necessary values can lead character undergraduate students to be superior . Valuechampion ( Honest , Fair , Authority , trustful , Religious and Accountable ) are the valuesinstilled in all students of the University of Sultan Agung Tirtayasa so that they can besuperior undergraduate and character . The purpose of this study is to determine how muchthe application of the values of a champion on students of Public Administration Faculty ofSocial Sciences University of Sultan Agung Tirtayasa . This research is quantitativedescriptive survey method . The respondents of this study as many as 100 people .Determination of respondents with incidental sampling . The results of this study indicatethat the application of the values of Champions at the State Administration of ScienceProgram Faculty of Social Untirta amounted to 78.75 % in both categories .